Glyoxal cross-linking of solubilized extracellular matrix to produce highly porous, elastic, and chondro-permissive scaffolds for orthopedic tissue engineering - Buckley, Conor; Dunne, Aisling; Kelly, Daniel (My University, 2019)
Extracellular matrix (ECM)-derived implants hold great promise for tissue repair, but new strategies are required to produce efficiently decellularized scaffolds with the necessary porosity and mechanical properties to facilitate regeneration. In this study, we demonstrate that it is possible to produce highly porous, elastic, articular cartilage (AC) ECM-derived scaffolds that are efficiently decellularized, nonimmunogenic, and chondro-permissive. Pepsin solubilized porcine AC was cross-linked with glyoxal, lyophilized and then subjected to dehydrothermal treatment. The resulting scaffolds were predominantly collagenous in nature, with the majority of sulphated glycosaminoglycan (sGAG) and DNA removed during scaffold fabrication. Four scaffold variants were produced to examine the effect of both ECM (10 or 20 mg/mL) and glyoxal (5 or 10 mM) concentration on the mechanical and biological properties of the resulting construct. When seeded with human infrapatellar fat pad-derived stromal cells, the scaffolds with the lowest concentration of both ECM and glyoxal were found to promote the development of a more hyaline-like cartilage tissue, as evident by increased sGAG and type II collagen deposition. Furthermore, when cultured in the presence of human macrophages, it was found that these ECM-derived scaffolds did not induce the production of key proinflammatory cytokines, which is critical to success of an implantable biomaterial. Together these findings demonstrate that the novel combination of solubilized AC ECM and glyoxal crosslinking can be used to produce highly porous scaffolds that are sufficiently decellularized, highly elastic, chondro-permissive and do not illicit a detrimental immune response when cultured in the presence of human macrophages
PUBLISHED
Keywords: Mesenchymal Stromal Cells; Cartilage; Cell source; Extracellular matrix; Scaffold; Decellularization; Tissue engineering; Immune response; Next Generation Medical Devices